Implementation of Qur'an Reading and Writing to Improve Students' ISMUBA (Al Islam, Kemuhammadiyahan, and Arabic Language) Learning at SMK Muhammadiyah Bumiayu - Legani, Daffa' Amanullah Putera; Listiani, Nisa Ahsanu; Juhaeroh, Juju; Rochmah, Siti Alfiatur; Jizmi, Ukhti Qowwiyul; Ansuhum, Sajid Rizqullah (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: The number of students who cannot read the Qur'an. Purpose: This study aims to obtain an overview of the implementation of the BTQ (Read and Write AlQur'an) program at SMK Muhammadiyah Bumiayu. Design/methods/approach: This research is categorized as field research which is included in qualitative research. Data collection was carried out using participant observation, documentation, and interview methods and using data analysis from sorted data, presented data, conclusions drawn. The feasibility and correctness of the data were tested by the presence of researchers, the triangulation method, discussions with peers and clarification of each piece of information. So on the basis of this, a BTQ program emerged at SMK Muhammadiyah Bumiayu which has been implemented and carefully planned with the school and is included in the compulsory extracurricular. In its application, it uses the Iqra' method, which is the method used in the BTQ program. Findings: Based on this application, it provides significant development for students related to the Reading and Writing Al-Qur'a program, namely in terms of student reading, making students fluent and Tartil and correct based on tajweed, sifatul huruf and makharijul huruf and improve students' understanding of ISMUBA (Al Islam, Kemuhammadiyahan, and Arabic Language) subjects. Research implications/limitations: The advice given to teachers is to be able to use varied and interesting methods so that learning is more interesting, effective and optimal. Originality/value: in terms of language, other researchers need to update and expand it from 3 parts, namely research design, content, and scope of study.